2016
DOI: 10.1111/jnc.13671
|View full text |Cite
|
Sign up to set email alerts
|

A role for amyloid precursor protein translation to restore iron homeostasis and ameliorate lead (Pb) neurotoxicity

Abstract: Iron supplementation ameliorates the neurotoxicity of the environmental contaminant lead (Pb); however, the mechanism remains undefined. Iron is an essential nutrient but high levels are toxic due to the catalytic generation of destructive hydroxyl radicals. Using human neuroblastoma SH-SY5Y cells to model human neurons, we investigated the effect of Pb on proteins of iron homeostasis: the Alzheimer's amyloid precursor protein (APP), which stabilizes the iron exporter ferroportin 1; and, the heavy subunit of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 101 publications
0
32
0
Order By: Relevance
“…Therefore, maintaining iron homeostasis can inhibit APP translation and Aβ overproduction by activating α-secretase [39]. On the other hand, it was reported that iron could promote APP translation to attenuate the toxicities of lead (Pb) [40], suggesting a protective role of iron in APP metabolism. In addition to the effects of iron on APP as mentioned above, APP could reversely affect iron, i.e., to stabilize the iron exporter FPN1, and the heavy subunit of the iron-storage protein, ferritin; by which the elevated APP can regulate metabolisms of brain and peripheral iron to attenuate brain iron elevation during aging [41].…”
Section: Ironmentioning
confidence: 99%
“…Therefore, maintaining iron homeostasis can inhibit APP translation and Aβ overproduction by activating α-secretase [39]. On the other hand, it was reported that iron could promote APP translation to attenuate the toxicities of lead (Pb) [40], suggesting a protective role of iron in APP metabolism. In addition to the effects of iron on APP as mentioned above, APP could reversely affect iron, i.e., to stabilize the iron exporter FPN1, and the heavy subunit of the iron-storage protein, ferritin; by which the elevated APP can regulate metabolisms of brain and peripheral iron to attenuate brain iron elevation during aging [41].…”
Section: Ironmentioning
confidence: 99%
“…Stably expressing cell lines overexpressing human wild-type APP695 isoform (SH-SY5Y APP 695 ) or the empty vector (pCEP4) were previously established (Venkataramani et al 2010). The stable SH-SY5Y cell line transfected with the APP 5 0 -UTR luciferase or HIRE_CAT constructs were described previously (Thomson et al 2005;Rogers et al 2016).…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…: E1500, Promega, Madison, WI, USA) was used according to manufacturer's directions to measure the luciferase activity. Reporter assays for balanced luciferase assays using the transfectants encoding the APP 5 0 -UTR luciferase (luc) reporter construct pGAL were as described previously (Rogers et al 2016). The activity of the Ferritin-H chain specific iron-responsive element (H-Ferritin IRE) was assessed using the plasmid construct, designated as HIRE_CAT, in which the H-Ferritin IRE had been ligated in front of a chloramphenicol acetyltransferase (CAT) reporter gene.…”
Section: Quantification Of Luciferase (Luc) and Chloramphenicol Acetymentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies were focused on the change of ion or trace elements concentration after lead exposure resulting in disturbance of brain function through an unclear pathway. Because lead is a divalent metal carries electronegativity and particle radius similarities with other ion or trace elements in the body [15,16], and its absorption, distribution could mimic other divalent trace elements such as iron, zinc, calcium etc. There is no available data to demonstrate the signi cant changes of divalent metal ion or trace elements in the brain after lead exposure.…”
Section: Introductionmentioning
confidence: 99%